Answer
777
Step-by-step explanation:
jnimimimimimim000
This is a function when u have f(n) u plug in the number for example 1 because the number -13 is the first number in the sequence
Answer:
y=(-5/3)x+29
Step-by-step explanation:
we will use the base formula y=mx+b
In order to be perpendicular, the slope must be the flipped fraction and have the opposite sign, so our m is (-5/3)
y=(-5/3)x+b
You can plug in the (9,14) point in order to find the b
14=(-5/3)(9)+b
14=(-45/3)+b
14=(-15)+b
14+15=b
29=b
and so altogether our equation is y=(-5/3)x+29
Answer:
a. A customer earns 1 free night per 10 nights stayed.
Step-by-step explanation:
The missing function is:
f(x) = x/10
The missing options are:
<em>
a. A customer earns 1 free night per 10 nights stayed. </em>
<em>
b. A customer starts with 1 free night and then earns another free night after every 10 nights stayed.
</em>
<em>
c.A customer earns x – 10 free nights for every 10 nights stayed. </em>
<em>
d. A customer earns 10 free nights after x number of nights stayed.
</em>
The function means that after a customer stayed 10 nights, a free night is earned. That is, replacing x = 10 into the function, we get:
f(10) = 10/10 = 1
which means 10 nights are equivalent to 1 free night.